From Fight or Flight, Freeze or Faint, to "Flow": Identifying a Concept to Express a Positive Embodied Outcome of Trauma Recovery. (May 2019) - Seng, Julia; Group, CAsCAid
BACKGROUND: The lifespan effects of adverse childhood experiences and their complex posttraumatic sequelae include early physical morbidity and mortality. Attention to physical sequelae and recovery is gaining clinical and research momentum. However, patient-centered communication in health care is hampered by lack of a common concept and word for a positive subjective, embodied outcome of trauma recovery.OBJECTIVE: To address this gap in theory, research, and practice vocabulary.DESIGN: We applied the six-step concept identification method described by Morse.RESULTS: The concept we identified is distinct from the trauma-reactive states of "fight or flight" and "freeze or faint." We call it "flow."CONCLUSIONS: Further deductive or inductive work to validate the concept would be useful as a step toward instrument development, followed by validation of its utility as a self-report proxy endpoint for patient centered health outcomes research. Qualitative research could be useful to elucidate the process of attaining "posttraumatic flow."